Гидравлические испытания клеевых соединений для узлов водоподготовки - Калинченко, М. Л.; Смахтин, В. В. (БНТУ, 2016)
Currently, all methods of permanent connection materials mainly used is welding. It is less time consuming and saves a lot of metal. In particular, the replacement of riveted joints welded allows to reduce the weight of the structure of carbon steels are 10 to 25% by reducing the cross-sectional areas of the connection. In addition, welding provides a particularly high degree of tightness of the joints. But in particular argon welding is expensive. When you work with it requires highly skilled professionals, and regular certification of equipment. In our study, we decided to replace the traditional method of connection (argon welding) the bonding in the manufacture of structural parts, namely, a slotted filter. The result of the work was manufactured an experimental model of the filter and carried out hydraulic tests.